History of Eugenics in Otorhinolaryngology: Ernst Rüdin and the International Eugenics Network - Beato Suwa (International Archives of Otorhinolaryngology, 2024)
Introduction The early geneticist and psychiatrist Ernst Rüdin (1874–1952) became one of the key figures in the eugenics movement and in the German health system of the Nazi era. His connections in the international eugenics network have played an important role in the history of eugenics.